Promoting Civic Engagement through Cultivating Culturally Competent Self-Reflexive Information Professionals. Issue 3 (2nd July 2020) - Singh, Rajesh
ABSTRACT: Although cultural diversity has been a growing discussion topic at conferences in recent years, the library and information science (LIS) profession remains in the gatekeepers of predominately white and female identities. Consequently, due to perpetual homogeneity and systemic institutional norms, some information professionals lack a deeper understanding of effective intercultural approaches and strategies to serve patrons who come from different cultural, socioeconomic, and religious backgrounds. This study demonstrates how information professionals can promote civic engagement by engaging in introspective reflections of their own identities and privileges. The qualitative content analysis of fourteen personal identity narrative papers from a recent 'Cultural Competence" course reveals how students' understanding on identity, privilege, oppression, and intersectionality evolved by self-exploring their own cultural identity narratives. This study addresses an approach to LIS education that calls for intentional efforts in developing experiential pedagogical approaches for facilitating critical self-reflection through coursework. Finally, it emphasises that self-reflexive information professionals equipped with cultural humility will go a long way in promoting civic engagement and building a more respectful, collaborative, cohesive, and culturally sensitive community.